Kaedah Penulisan Tafsir Di Malaysia: Kajian Terhadap Tafsir Pedoman Muttaqin - Amran Abdul Halim; Walid Mohd Said; Nidzamuddin Zakaria; Amiruddin Mohd Sobali; Abdulloh Salaeh; Mohd. Fauzi Mohd. Amin; Ahmad Kamel Mohamed; Syed Najihuddin Syed Hassan; Mahsor Yahya; Tengku Fathul Aziz Tengku Abd Mutalib (Universiti Sains Islam Malaysia, 2024)
PAPER PROCEEDINGS THE 7TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION (SWAT) 2021 “ISLAMIC AND NON-REVEALED KNOWLEDGE IN FACING THE GLOBAL CHALLENGES” 6th – 7th October 2021 / 29 – 30 Safar 1443H Faculty of Quranic and Sunnah Studies Universiti Sains Islam Malaysia